The Role of Caste in Prostitution: Culture and Violence in the Life Histories of Prostitutes in India - Rozario, Mary Rita (1998)
The caste system prevalent in Indian society has never been studied with respect to its role in prostitution. This critical and analytical study of the role of caste in prostitution in India is the result of over thirty years of observation both within the institution of prostitution, that is, in its ‘internal’ relationships; and outside the institution in the ‘external’ relationships which create violence in the lives of prostitutes in India. The caste system which plays a major role in the life of Indians has a role in prostitution yet this issue remains unexplored by scholars. Even when focusing on Scheduled Caste women, amongst whom most prostitutes number, the issue treated has been mainly that of economics, rather than those of culture and violence in their lives. The scope of study is restricted to women and girls alone, in keeping with the focus of the services of the Good Shepherd sisters (of whom the author is one) throughout the world. Under the prevailing caste system people are stratified into groups and the relationships among them is specified. The Scheduled Caste is one of the groups that exist outside the caste system in India and it numbers 138.2 million (Census India 1991). This study is based on three pairs of dichotomous concepts: the ‘Upper Castes’(the ‘pure’) and the Scheduled Castes (the ‘impure’); the males (the ‘supreme’ gender) and the females (the ‘inferior’ gender); male sexuality contextualized as the ‘human sexuality’ and female sexuality conceptualized as ‘good’ and ‘evil’ with dual perception. It indicates how persons are casteized, genderized and sexualized in the Indian society. It highlights parallels between the Upper Castes’ domination (concentration and exercise of power) over the Scheduled Castes (or the ‘Untouchables’) and between the lower position held by the Scheduled Castes and their experience of violence in Indian society. The data of my study consists of that gathered by interviewing prostitutes in specific surveys (three studies from 1983-90) and also from my practical experience of working with women and girls in prostitution for two decades (1962-82). The analysis of prostitution is set against the accepted wisdom which perceive the entry of all women and girls into prostitution for economic reasons, and against the Indian situation in which the country still faces the problems of dehumanized Scheduled Castes and grinding poverty. To see prostitution as a consequence of economic necessity, though accepted in many societies, remains controversial in the context of Indian society. In some societies prostitution is a form of labour and the economic cause is argued on the basis of financial autonomy, self-determination and occupation of choice for women. This study takes the stance that economic arguments alone are not universally acceptable and are generally not appropriate to the whole range of the entry of Scheduled Caste women and girls in prostitution in India. My study attempts to fill the gap left by previous studies by using my experience and an evaluation of a sample of women and girls in prostitution from various cultural backgrounds to illustrate the effectiveness of culture and violence in the lives of Indian prostitutes. The caste structure not only stratifies the Indian society, but also defines status, relationships and sexuality. This has major implications for the issues of power and violence between groups as they relate to one another. There exists a web of relationships between culture-violence-power that uses culture to mask violence; the 'internal'-'external' relationships which involve controlling and rejecting assimilation of prostitutes in the mainstream of life in society creating violence; the bond of friendship between the Upper Caste/Class men and women in the prostitute world which leads to exploitation of the Scheduled Caste women and girls; the exploitation of women by women for their survival; the role of caste and the dynamics of culture that contribute to the perpetuation of prostitution in India. The upper caste/class clients forming the first clients and patrons to exploit the girls, the caste/class nexus characterized by accumulation of power, and domination and subordination, and the strategy adopted for the diffusion of the Scheduled Caste violence (i.e. retaliation of the Scheduled Castes for exploiting their women and girls by the Upper Castes) which makes the Scheduled Caste girl into a ‘sacrificial victim’ in Indian society. These form the major findings of this study